THE IMPACT OF SPORT ON PCOS - Justyna Goryczka; Magdalena Lisik; Urszula Majda; Magdalena Michalik; Magdalena Mida; Anna Maruszak; Julia Kwiecień; Julia Stołtny; Natalia Hajok; Witold Kimla (International Journal of Innovative Technologies in Social Science, 2026)
Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women of reproductive age and has a significant impact on a wide range of metabolic, hormonal, and psychosocial disturbances. Symptoms of PCOS include menstrual irregularities, hyperandrogenism, infertility, overweight or obesity, as well as an increased risk of insulin resistance and cardiovascular disease. Numerous scientific studies emphasize the important role of regular physical activity as a non-pharmacological treatment strategy in women with PCOS. The aim of this article is to evaluate the impact of regular physical activity on the course of PCOS, with particular emphasis on metabolic and hormonal parameters, body composition, physical fitness, and quality of life in women affected by this condition. A review of the available literature indicates that both aerobic and resistance training, when performed regularly and at appropriate intensity, have a significant positive effect on improving insulin resistance, cardiorespiratory fitness, and body composition, contribute to reductions in body fat, and reduce the severity of clinical symptoms of PCOS. Additionally, regular physical activity reduces the occurrence of both anxiety and depressive symptoms, thereby exerting a beneficial effect on mental health. The obtained data confirm that participation in sports and engagement in regular physical activity constitute an important element of comprehensive therapeutic management in women with PCOS and should be considered a fundamental form of supportive treatment.